Strategi Pengurangan Kerugian Produk Kedaluwarsa Ritel Melalui Implementasi Aplikasi IoT Penjaga Inventaris Digital - Wijaya, Herri; Irawati, Fifi Endah; Akbar, Milad Nufal (Universitas Prasetiya Mulya, 2026)
This study addresses inventory inefficiencies and financial losses from expired product waste in Micro, Small, and Medium Enterprises (MSMEs). Capital constraints often prevent MSMEs from adopting corporate-scale Internet of Things (IoT). We investigate a Frugal IoT approach integrated with digital nudging through a mobile application,